2016
DOI: 10.1182/blood-2016-02-698027
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 activates mTOR and primes stress-activated gene expression leading to prolonged antitumor capacity of NK cells

Abstract: Key Points Cytokine-activated NK cells display distinct gene expression programs in response to cytokine withdrawal. IL-15 sustains antitumor functions of NK cells through mTOR-governed metabolic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 56 publications
14
120
1
1
Order By: Relevance
“…These pathways were robustly induced by IL-15 in the CD56 bright NK cell subset, and their blockade significantly impaired priming. This finding is consistent with studies investigating murine NK cell cytotoxicity (50), whereas reports concerning human NK cell cytotoxicity have been conflicting (38,50,65), specifically with regard to the role of mTOR. Similar to reports from another group (38), we found that pretreatment of NK cells with the mTOR inhibitor Torin1 at concentrations that selectively inhibit mTORC1/2 (10 nM) prior to priming did not impact effector responses (CD107a, IFN-γ, TNF) of CD56 bright or CD56 dim NK cells against K562 targets, or impair cytotoxic protein upregulation.…”
Section: 5supporting
confidence: 88%
See 1 more Smart Citation
“…These pathways were robustly induced by IL-15 in the CD56 bright NK cell subset, and their blockade significantly impaired priming. This finding is consistent with studies investigating murine NK cell cytotoxicity (50), whereas reports concerning human NK cell cytotoxicity have been conflicting (38,50,65), specifically with regard to the role of mTOR. Similar to reports from another group (38), we found that pretreatment of NK cells with the mTOR inhibitor Torin1 at concentrations that selectively inhibit mTORC1/2 (10 nM) prior to priming did not impact effector responses (CD107a, IFN-γ, TNF) of CD56 bright or CD56 dim NK cells against K562 targets, or impair cytotoxic protein upregulation.…”
Section: 5supporting
confidence: 88%
“…Similar to reports from another group (38), we found that pretreatment of NK cells with the mTOR inhibitor Torin1 at concentrations that selectively inhibit mTORC1/2 (10 nM) prior to priming did not impact effector responses (CD107a, IFN-γ, TNF) of CD56 bright or CD56 dim NK cells against K562 targets, or impair cytotoxic protein upregulation. Priming-induced increases in antitumor effector responses and cytotoxic protein levels were, however, impeded by Torin1 at concentrations of 1 μM, similar to what has been used in other studies (65). However, micromolar concentrations result in off-target effects, including inhibition of PI3K (51 Proliferation and viability assays.…”
Section: 5mentioning
confidence: 73%
“…Though other studies have highlighted a positive role for mTOR signaling in NK cell function (19,21), NK cells were treated with IL-15 for a short duration (12-48 hours), thus inducing only a brief priming stimulus. These studies did not explore continuous dosing with multiple doses of IL-15, and thus, the resulting functional exhaustion and negative input of excessive mTOR signals was not seen.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 has also been implicated in cytokine-driven NK cell proliferation during development and activation with high concentrations of IL-15 (20). A separate study showed that IL-15 activates mTOR, leading to prolonged antitumor NK cell capacity (21). In both of these studies mTOR inhibition led to decreased NK cell functionality.…”
Section: Introductionmentioning
confidence: 98%
“…Нещодавно описана безпосередня роль TOR1 в посиленні мітохондріального окисного фосфори-лювання, а також роль TOR1 в регуляції продукції вільних радикалів мітохондрією [13,17]. Таким чи-ном, з одного боку, вільні радикали регулюють ак-тивність TOR1, а з іншого -TOR1 регулює продук-цію вільних радикалів мітохондрією і спрягає гліко-ліз із метаболізмом мітохондрії [14].…”
unclassified